Characterization of mixed mode fracture properties of nanographene reinforced epoxy and Mode I delamination of its carbon fiber composite. (1st February 2018) - Kumar, Abhishek; Roy, Samit
Abstract: Motivated by previous research performed by the authors investigating Mode I toughness enhancement using nanographene in EPON 862 epoxy, this article aims to investigate (a) the changes in mixed mode fracture properties of a thermoset polymer (EPON 862) reinforced with hydrogen passivated nanographene platelets (HP-NGPs) and, (b) Mode I fracture properties of EPON 862/IM7 unidirectional laminate with and without dispersed HP-NGPs. For (a), mixed mode fracture experimentation was performed using an asymmetric four-point bending specimen on baseline (0 wt%), 0.1 wt% and 0.5 wt% HP-NGP reinforced EPON 862 polymer. Three different mode mix (KII /KI ) ratios (0.78, 1.53, 117) were used to obtain an experimental fracture envelop encompassing pure Mode I to Mode II. Remarkable increase in the fracture envelop both in Mode I (∼3 times) and Mode II (∼2.5 times) was observed with only 0.5 wt% of HP-NGP. For case (b), Double Cantilever Beam (DCB) experiments were used to obtain the fracture toughness of the unidirectional laminates with the HP-NGP reinforced matrices as in (a), in accordance with ASTM D5528. Significant increase (∼100%) in resistance to crack propagation was observed for 0.5 wt% NGP reinforced system in comparison to baseline samples.